Mechanical properties and microstructure of molybdenum coating layers deposited vacuum plasma spray process - Mihailo Mrdak; Časlav Lačnjevac; Marko Rakin; Nikola Bajić (Zaštita Materijala)
Molybdenum coatings due to their excellent wear resistant properties and sliding characteristics under dry friction conditions are often used in applications to resist friction and dry sliding. Since molybdenum metal is susceptible to oxidation, in this study, the molybdenum coating layers were successfully deposited at low pressure inert gas Ar using vacuum plasma spray technology (VPS). Characterization of the Mo coating was performed by measuring the microhardness of the coating layers using the Vickers HV0.3 method, the bond strength by tensile testing and the microstructure by optical microscopy (OM) and scanning electron microscopy (SEM). The microstructure of the coating layers was tested in deposited stateand after etching. The etching reagent used was NH3·H2O and H2O2 with a volume ratio of 1:2. The results showed that the coating has good mechanical properties, microhardness and high adhesion/cohesion strength. Layers of VPS - Mo coatings were composed of well-melted powder particles, partially unmelted particles with a good bond in the coating layers and micropores with a share below 0.5%. It was found that the microstructure of the coating consists mainly of lamellar structure and columnar crystal Mo grains. Tests have shown that the VPS - Mo coating layers have mechanical characteristics and a microstructure which fully enables the use of the coating on surfaces of parts which are required to have good sliding properties, resistance to wear and corrosion.